Wideband N-Beam Arrays Using Low-Complexity Algorithms and Mixed-Signal Integrated Circuits - Perera, Sirani M.; Ariyarathna, Viduneth; Udayanga, Nilan; Madanayake, Arjuna; Wu, Ge; Belostotski, Leonid; Wang, Yingying; Mandal, Soumyajit; Cintra, Renato J.; Rappaport, Theodore S. (IEEE journal of selected topics in signal processing, 2018)
This paper proposes a low-complexity wideband beamforming subarray for millimeter wave (mmW) 5G wireless communications. The multibeam subarray is based on using a novel delay Vandermonde matrix (DVM) algorithm to efficiently generate analog true-time-delay beams that have no beam squint. A factorization for the DVM leading to low-complexity analog realizations is provided and complexity analysis for real and complex inputs is derived. The DVM is a special case of a Vandermonde matrix but with complex nodes that lack any special properties (unlike the discrete Fourier transform matrix). Error bounds for the DVM are established and then analyzed for numerical stability. Mixed-signal CMOS integrated circuits designs are proposed for the implementation of DVM multibeam algorithms along with low-complexity digital realizations to achieve hybrid beamforming for mmW applications. Analog-digital hybrid mmW multibeam beamforming circuits and systems are designed, for example, with eight beams at 28 GHz and simulated in cadence for functional verification.